Don Juan : or Two and two equals four or Lust is the only swindle I wish permancence - Ursula Blickle Stiftung, Nürnberg; Kunsthalle Wien (Kraichtal; Nürnberg; Wien : Kunsthalle Wien; Ursula Blickle Stiftung Kraichtal; Verlag für moderne Kunst Nürnberg, 2006)
Cantor, Ellen ; Dolven, Anne Katrine ; Geers, Kendell ; Haug, Helgard ; Hirakawa, Noritoshi ; Koganezawa, Takehito ; Lilli & Lola ; Moffatt, Tracey ; Monroe, Vlad ; Naskovski, Zoran ; Pobitzer, Klaus ; Rondinone, Ugo ; Rose, Tracey ; S-338 ; Seror, Kiki ; Solomons, Doron ; Taylor-Wood, Sam ; Wetzel, Daniel ; Wurm, Erwin
2 ex. (engels & duits)
Don Juan in Film since 1953, Don Juan in literature since 1953 p. 134-135
biog., tent. p. 136-141
Engels
Exhibition. Don Juan : Two and two equals four or Lust is the only swindle I wish permanence (1). Exhibition. Don Juan : Two and two equals four or Lust is the only swindle I wish permanence (2). Kunsthalle Wien. Ursula Blickle Stiftung Kraichtal. 2006-03-12. 2006-03-25. 2006-04-16. 2006-04-23
boek